Comparison of Fermentation Kinetics of Milk Kefir and White Rice Kefir at Low Temperatures: Exploring the Effects on Product Quality - Neneng Windayani; Rina Budi Satiyarti; Ira Sukmawati Abidin; Muhammad Maulana Mansur; Ahmad Zaenal Ependi; Linda Lisdiana; Fransisca Amelia Yusuf; Adi Muhammad Nurdiansyah; Intan Junia Anggara; Putri Widia Mukti; Robby Nur Hidayat; Erza Aulia; Wan Saidatul Syida Wan Kamarudin (Pandawa Institute, 2024)
Kefir fermentation has been extensively studied because of its potential to develop novel functional drinks and its various biological activity. This study investigates the comparative fermentation kinetics of milk kefir and white rice kefir at low temperatures, addressing a gap in current research. Utilizing a comprehensive research methodology, including sample preparation, fermentation processes, and various analyses, the study explores the distinct patterns observed in the fermentation kinetics, physicochemical properties, and microbiological characteristics of both kefir types. The results highlight significant differences influenced by low temperatures, emphasizing the need to consider specific attributes for each kefir type in low-temperature fermentation. The findings contribute novel insights into optimizing fermentation conditions and enhancing product quality. The results offer additional perspectives on the influence of fermentation temperature on microbial dynamics, physicochemical properties, and health-related aspects in various fermented products. This study advances our understanding of kefir fermentation, providing valuable implications for the production of high-quality and functional beverages.